What is the driving force? Urban regions: between innovative milieus and urban governance - Ache, Peter (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
Great expectations are currently being pinned on towns and urban regions with regard to the crucial part ascribed to them in shaping the competitive environment in both European and global terms. They are the “engines” which deliver creative solutions and perform myriad feats of integration regarded as vital to maintaining economic competitiveness. The theoretical debate on the functioning of regional economies reflects this view and is constantly increasing the number of aspects which it includes in its model studies. Two examples are the local innovative milieu investigated by the GREMI research group, and the discussion on urban governance. Both models are concerned with the description and analysis of structures and actions in regions and towns. Irrespective of differences between the specific norms which apply to the two models, in a more fundamental sense these are the issues of the future: Faced with the complexity of the competitive environment, how will it be possible for urban regions to create and to maintain the ability to shape themselves?